1991
DOI: 10.1111/j.1365-2265.1991.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of bromocriptine after long‐term therapy for macroprolactinomas; effect on plasma prolactin and tumour size

Abstract: The present study describes the effect on plasma prolactin values and tumour size of bromocriptine withdrawal in 12 patients who had been treated for macroprolactinomas for a period of 3.5-7 (mean 4.9) years. Pretreatment plasma prolactin values ranged from 12,000 to 210,000 (mean: 66,000) mU/l. Immediately before bromocriptine withdrawal plasma prolactin values were in the normal range (less than 350 mU/l for men; less than 450 mU/l for women). Bromocriptine treatment was associated with tumour reduction in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 17 publications
1
25
3
6
Order By: Relevance
“…These outcomes are better than usually been reported (mean 29%, ranging from 7 to 69% [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussioncontrasting
confidence: 42%
“…These outcomes are better than usually been reported (mean 29%, ranging from 7 to 69% [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussioncontrasting
confidence: 42%
“…Of the 30 patients whose PRL levels fell to normal levels, 21 maintained the condition with low-dose bromocriptine (0.625-10 mg/d), and their PRL levels and tumor volumes were well controlled. According to the reports of bromocriptine withdrawal [32][33][34][37][38], 14 patients with normal PRL level and absent tumor on MR images withdrew from bromocriptine treatment in our group, and renewed tumor growth and recurrent hyperprolactinemia were not found during an average period of 1.5-year follow-up. About 18 patients with residual tumor invading the cavernous sinus had no related compromising symptoms, of which seven patients maintained normal PRL levels with low-dose bromocriptine treatment.…”
Section: Bromocriptine Reduction or Withdrawalcontrasting
confidence: 48%
“…vanЈt Verlaat et al (6) observed reduction of tumor nests and also acellular spaces. They also speculate that BRC might have a cytostatic effect related to short-term therapy, and a cytocidal one to long- term therapy, and suggest that this finding may explain the maintenance of normoprolactinemia after drug withdrawal.…”
Section: Discussionmentioning
confidence: 97%